Avaliação in vitro da resistência de união de dois sistemas adesivos dentinários à dentina bovina antes e após a termociclagem: teste de cisalhamento e análise estereomicroscópia - Amendola, Alessandra Buhler [UNESP] (1999)
The aim of fhe present study was to investigate the shear bond strength of two adhesive systems, Scotchbond Multi-Purpose Plus (3M) and Etch & Prime 3.0 (Degussa), to bovine dentin, before and after thermal cycling. Bovine incisors were embedded in self-cured resin and labial dentin surfaces were ground with sequential abrasive sandpapers. The specimens were separated into two groups to receive the adhesive systems. A composite resin cylinder (Z100-3M) was bonded to the dentinal surface. The two groups were divided into two more groups (A and B). The subgroup A was shear tested after 24h and the subgroup B was subjected to 500 thermal cycles, between 5ºC and 55ºC, with a dwell time of 30 seconds and, then, shear tested. The bond strength was performed on a Universal lnstron machine 4301, with a load cell of 500 Kg and a speed of 0,5mm/min. The mode of failure were classified. The analysis of variance (ANOVA), at 5% significant level, revealed that there were no significant differences among the bond strength of the two adhesive systems, and that the thermal cycling did not significantly influence strength of the two materials tested. The Scotchbond Multi-Purpose Plus showed a considerable number of adhesive failures and the Etch & Prime 3.0 showed predominantly mixed fractures, followed by adhesive fractures